2011
DOI: 10.17221/68/2010-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of apricot cultivars by random amplified polymorphic DNA and microsatellite primers

Abstract: Chroboková E., Raddová J., Vachůn M., Krška B., Pidra M., 2011. An analysis of apricot cultivars by random amplified polymorphic DNA and microsatellite primers. Hort. Sci. (Prague), 38: 125-133.The random amplified polymorphic DNA (RAPD) technique and microsatellites were used to study the genetic diversity and to identify cultivars within a collection of 95 cultivars of Prunus armeniaca L. A dendrogram based on 13 RAPD primers and a dendrogram based on 9 microsatellite primers were prepared using the unweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Additionally, our cultivars were classi ed into two main groups, including the pink and the white cultivars respectively, the genetic distances among them varied from 0.03 to 0.24, with similarity to the previous research results in apricot and cowpea (Chroboková et al 2011;Masvodza et al 2014).…”
Section: Introductionsupporting
confidence: 85%
“…Additionally, our cultivars were classi ed into two main groups, including the pink and the white cultivars respectively, the genetic distances among them varied from 0.03 to 0.24, with similarity to the previous research results in apricot and cowpea (Chroboková et al 2011;Masvodza et al 2014).…”
Section: Introductionsupporting
confidence: 85%
“…Baránek et al (2006) suggested that NorthAmerican cultivars originated by hybridization between European and Asian apricots. Chroboková et al (2011) demonstrated that in RAPD dendrograms, the cultivars were classified into five groups, according to their geographic origin: hybrids originated by hybridization among cultivars of European and Asian origin, European cultivars, American cultivars, Asian cultivars and interspecific hybrids.…”
Section: Fig 3 Dendrogram Using Average Linkage (Between Groups)mentioning
confidence: 99%
“…Union for the Protection of New Varieties of Plants (UPOV) observes that SSR markers are more suitable for DNA profiling because of their multi-allelic nature, reproducibility, high polymorphism, easy automation, and co-dominant nature of inheritance (UPOV/INF/17/1 2010 guideline). SSR markers are widely applied in genotyping of species (Chrobokova et al 2011;Behera et al 2012;Koussao et al 2014) and in cultivar identification (Liu et al 2014;Basheer-Salimia et al 2014). In turmeric, limited work is reported so far on molecular characterization, using SSR markers (Siju et al 2010;Joshi et al 2010;Khan et al 2013;Singh et al 2015) aiming largely at diversity assessment, accessions of cultivars, and not for cultivar identification.…”
Section: Introductionmentioning
confidence: 99%